Analysis of Factors Influencing Adoption of Technology in Cocoa Pod Borer Pest Control: A Case Study in West Sulawesi - Herman .; Parulina Hutagaol; Suharjono H Sutjahjo; Aunu Rauf; D. S Priyarsono (Indonesian Coffee and Cocoa Research Institute, 2006)
Cocoa pod borer is one of the most difficult pests to be controlled, hence it becomes serious threat for sustainable cocoa plantation. The objective of the research is to investigate several factors influencing adoption of innovation technology in pest control by using regression model analysis. The research was carried out in Polewali Mamasa and Mamuju regency, West Sulawesi during February March 2006 using survey method. Number of respondents interviewed in the research was 80 people which was selected by using purposive sampling method. The result shows that CPB in West Sulawesi decreased cocoa productivity 50% (10—90%), caused by less of farmers coordination in controlling CPB and the slowness of technology adoption. Factors which influence farmer's knowledge are provision of field school, farmers income and simplicity of the technology. Factors which influence farmer's attitude are farmer's income knowledge, cultivated cocoa area, provision farmer's group and number of family members. Factors which influence farmer action in PsPSP technology adoption is farmer attitude, farmer income, cultivated cocoa area and availability of extension workers in that area. Government’s involvement in accelerating adoption of innovation technology, especially in preparing capable extension workers and provision of subsidized credit for the farmers is inevitable. Key words: cocoa pod borer, adoption of technology, sustainable cacao plantation, Government’s involvement, West Sulawesi